Characteristics of three low grasslands with different rest periods (Semiárida, 2020)
In an upland region with short grassland in the Dpto Loventué- La Pampa (Lat-.36°50' S Long.65°18' W) we compared three areas-. Two of them were exclosures of 28 and 14 years; the third had a rest of twelve months every other year. The three communities were similar in floristic composition but different in the values of abundance-cover of their principal species. Vegetation cover had a maximum in the exclosures and a minimum in the area that had a rest of twelve months every other year. In the three areas the frequency of dominants and codominants species ranged among 90-100%. Standing crop reached 320 gMS/m2 in the oldest exclosure and 150 gMS/m2 in the area with a rest of twelve months every other year. Flower stalk numbers, culm lenght and crown diameter were great in the 14 years exclosure·.koeleria permollis a decreaser palatable specie was codominant only in the 28 years exclosure. Poa ligularis another decreaser desiderable specie codominated in the 14 years exclosure. In the area with a rest of twelve months every other year was dominant Piptochaetium.
Keywords: grassland; La Pampa